Location decisions in a changing labour market environment - Björn Frank (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
We study the location of various film-related services (such as camera rental, casting agencies or pyrotechnic services), the main determinant of interest being the human capital specificity. We show that firms which supply services with a lower firm specificity locate farther away from one another, and argue that it can be concluded that the "poaching" argument (fear of employees leaving for a competitor in large regional labour markets) has greater practical weight than the Marshallian labour pooling mechanism.
Keywords: R30; J41; J63; L82; 330; agglomeration; film industry; flexible specialisation; labour pooling; poaching; regional labour markets; turnover; Standortwahl; Filmwirtschaft; Ballungsraum; Regionaler Arbeitsmarkt; Regionale Arbeitsmobilität; Schätzung; Deutschland